2002
DOI: 10.1021/jm0208673
|View full text |Cite
|
Sign up to set email alerts
|

Novel Structures Derived from 2-[[(2-Pyridyl)methyl]thio]-1H-benzimidazole as Anti-Helicobacter pylori Agents, Part 1

Abstract: 2-[[(2-Pyridyl)methyl]thio]-1H-benzimidazoles (2, sulfides) exhibit antibacterial properties that are selective for Helicobacter spp., but they also have an inherent susceptibility to metabolic oxidation to furnish 2-[[(2-pyridyl)methyl]sulfinyl]-1H-benzimidazoles (1), which act as proton pump inhibitors (PPIs). We have discovered five compounds with retained antibacterial potency and selectivity in which the overall framework of the sulfides 2 could be kept intact while structural modifications were made to r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 43 publications
(70 reference statements)
0
32
0
2
Order By: Relevance
“…Benzimidazole derivatives shows a very good anti bacterial activities [10][11][12][13][14], we are comparing the synthesized new benzimidazole derivatives to the marketed chlorophenicol [15] which shows very good anti bacterial activity, here we are synthesizing the newly substituted benzimidazole derivatives for the studies of antibacterial activities by comparison with the drug molecule. In this studies compound 3f shows good bacterial activity, in which the tertiary butyl group is the electron releasing group, which is attached to the para position.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Benzimidazole derivatives shows a very good anti bacterial activities [10][11][12][13][14], we are comparing the synthesized new benzimidazole derivatives to the marketed chlorophenicol [15] which shows very good anti bacterial activity, here we are synthesizing the newly substituted benzimidazole derivatives for the studies of antibacterial activities by comparison with the drug molecule. In this studies compound 3f shows good bacterial activity, in which the tertiary butyl group is the electron releasing group, which is attached to the para position.…”
Section: Resultsmentioning
confidence: 99%
“…Literature survey has also revealed the importance of benzimidazoles as antimicrobial and antioxidant agents [10][11][12][13][14]. It has also been reported that certain substituted benzimidazole derivatives have a broad antimicrobial spectrum [11].…”
Section: Introductionmentioning
confidence: 99%
“…Also, the compounds whose molecules possess an azole ring, such as pyrrole [11][12][13], 1,3,4-oxadiazole [14][15][16][17][18][19] and 1,2,4-triazole [19][20][21][22][23], are often characterized as good antimicrobial agents. In our previous works [24][25][26][27], we have reported that the heating under reflux of 4-(1H-benzimidazol-2-yl)-1-(substituted phenyl)pyrrolidin-2-ones in a 20% aqueous sodium hydroxide solution leads to the opening of the 2-pyrrolidinone cycle, followed by the formation of sodium salts of the corresponding N-substituted γ-amino acids.…”
Section: Introductionmentioning
confidence: 99%
“…Substituted benzothiazoles and benzimidazoles have found application in a wide range of therapeutic areas such as antiulcers, anticancers, antihistamics, antifungals, and antivirals to name a few. [1][2][3][4][5][6][7][8][9][10] The chemistry of azaazulenes 11 is of interest for their physiological properties 12,13 as well as physical and chemical properties. Therefore, it is expected that benzazolyl-1-azaazulenes have potential bioactivities.…”
Section: Introductionmentioning
confidence: 99%